Apresentação - Oliveira, Daniela Garces de; Viegas, Danielle Heberle; Karpowicz, Débora Soares; Moreno, Eduard Esteban; Nascimento, Fernanda de Santos; Munareto, Geandra Denardi; Miranda, José Augusto Ribas; Oliveira, Luciana da Costa de; Peixoto, Maitê; Vianna, Marcelo; et al. (Oficina do Historiador, 2014)
Apresentação da Equipe Editorial - Volume 7, número 1.